A building contract casebook - Powell-Smith, Vincent (BSP Professional Books, 1990)
Brings together the leading cases on building contracts, together with many lesser known decisions which establish or illustrate the legal principles. For each case there is a succinct statement of the principle established, a summary of the facts and the decision.